Comparison of several methods of stands inventory prior to logging towards the yield volume of mangrove forest in Bintuni Bay, West Papua Province, Indonesia - Dr. Istomo; Cecep Kusmana; Fifi Gus Dwiyanti; Zulfikar Malik (Society for Indonesian Biodiversity, 2020)
Abstract. Istomo, Kusmana C, Dwiyanti FG, Malik D. 2020. Comparison of several methods of stands inventory prior to logging towards the yield volume of mangrove forest in Bintuni Bay, West Papua Province, Indonesia. Biodiversitas 21: 1438-1447. The difference between the estimated volume and the actual harvested volume is the reason that mangrove forest management is unsustainable. To overcome this discrepancy, it is important to do what so called Inventarisasi Tegakan Sebelum Penebangan (ITSP) or stands inventory prior to logging for logging concession. However, the study on suitable ITSP methods for mangrove forests has been limited. This study aims to assess three ITSP methods (namely Line Strip Sampling Method, Line Systematic Sampling Method, and CIFOR’s Modified Method) using two allometric equations (i.e., equation developed specifically by a logging concession and equation developed that has specific formula for each species), and to select the combination of method and allometric equation that produce the highest accuracy for logging concession in mangrove forest, especially in Bintuni Bay, West Papua. The results showed that CIFOR’s Modified Method produces the lowest discrepancy between the estimated volume and the actual harvested volume, followed by Line Strip Sampling Method. In addition, regardless the ITSP methods employed, the allometric equation by Cole et al. (1999) outperforms the equation developed specifically by a logging concession. While producing the lowest discrepancy with plot size is the smallest than other methods, CIFOR’s Modified Method has a disadvantage when applied in the field due to difficulties in making a circular plot. As such, we recommend ITSP method to be used is the Line Strip Sampling method with allometric equation.